Contraceptive use and fertility in Gujarat - Visaria, Pravin M. (Gujarat Institute of Development Research, 1992)
Study of contraceptive use and fertility in Gujarat based on survey of four districts is product of collaborative project of the Gujarat Institute of Development Research & Population Council, New York.